The Influence of Automated Interactions on Consumer Purchase Decisions Across the Customer Journey: A Systematic Literature Review - Hylman Jatmiko Nur Wicaksana; Zulfikar Fauzi (Journal of Applied Digital Business Management, 2025)
This systematic literature review investigates how automated interaction such as chatbots, voice assistants, and conversational messaging platforms shape consumer purchase decisions across the stages of the customer journey. Drawing on 13 empirical studies published between 2010 and 2024, the review highlights consistent evidence that automated systems enhance awareness by increasing engagement and social presence; strengthen consideration by improving information quality and personalized recommendations; streamline purchase processes through reduced friction and guided flows; and reinforce post-purchase outcomes via efficient service and emotional responsiveness. Nevertheless, their effectiveness depends on technological sophistication, transparency, privacy management, and contextual relevance. Methodological gaps include limited longitudinal studies, varying measurement approaches, and insufficient exploration of ethical concerns. This review proposes an integrative framework that connects automated interaction mechanisms with consumer behavior dynamics across journey stages.